2014
DOI: 10.1016/j.jtcvs.2013.02.037
|View full text |Cite
|
Sign up to set email alerts
|

The Ross procedure in patients aged less than 18 years: The midterm results

Abstract: The low rate of autograft failure demonstrates that the Ross procedure is an attractive option for the management of aortic valve disease and complex left ventricular outflow tract obstruction in the pediatric population. However, alternative options must be considered in adolescents and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…In our assessment of survival, we found that the neonate/infant group had the highest mortality rate. Our 29% in-hospital mortality rate for neonates is comparable with other modern series with reported mortality ranging from 12% to 75% [9,[17][18][19]. No prior studies have reported on long-term survival for infants after the Ross procedure.…”
Section: Commentsupporting
confidence: 78%
See 3 more Smart Citations
“…In our assessment of survival, we found that the neonate/infant group had the highest mortality rate. Our 29% in-hospital mortality rate for neonates is comparable with other modern series with reported mortality ranging from 12% to 75% [9,[17][18][19]. No prior studies have reported on long-term survival for infants after the Ross procedure.…”
Section: Commentsupporting
confidence: 78%
“…Previous series have reported 74% to 100% freedom from LVOT reintervention in pediatric Ross patients at 10 years; however, nearly all comprised mixed age group cohorts [6,9,15,19].…”
Section: Commentmentioning
confidence: 97%
See 2 more Smart Citations
“…Observational study (9,(14)(15)(16)18) and more recent randomized study controlled (23)(24)(25) have updated the previous work by including higher-risk patients and reflecting changes in clinical and surgical practice. These studies included large numbers of patients with different aortic disease pathogenesis who were treated with reinforcement of pulmonary autograft (23)(24)(25)51).…”
Section: Evidence From Trials and Observational Studiesmentioning
confidence: 99%